Association of Drusen Volume with Choroidal Parameters in Non-Neovascular Age-Related Macular Degeneration - Balasubramanian, Siva (Retina, 2017)
PURPOSE: The choroid is thought to be relevant to the pathogenesis of non-neovascular age-related macular degeneration (NNVAMD), but its role has not yet been fully defined. In this study, we evaluate the relationship between the extent of macular drusen and specific choroidal parameters, including thickness and intensity. METHODS: Spectral-domain optical coherence tomography (SD-OCT) images were collected from two distinct, independent cohorts with NNVAMD: Amish (53 eyes of 34 subjects) and non-Amish (40 eyes from 26 subjects). All SD-OCT scans were obtained using the Cirrus HD-OCT with a 512 × 128 macular cube (6x6mm) protocol. The Cirrus advanced RPE analysis tool was used to automatically compute drusen volume within 3 mm (DV3) and 5 mm (DV5) circles centered on the fovea. The inner and outer borders of the choroid were manually segmented and the mean choroidal thickness (CT) and choroidal intensity (CI; i.e. brightness) were calculated. The CI was normalized against the vitreous and nerve fiber layer reflectivity. The correlation between DV and these choroidal parameters was assessed using Pearson and linear regression analysis. RESULTS: A significant positive correlation was observed between normalized choroidal intensity (NCI) and DV5 in the Amish (r = 0.42, p = 0.002) and non-Amish (r = 0.33, p = 0.03) cohorts. Also, DV3 showed a significant positive correlation with NCI in both the groups (Amish: r = 0.30, p = 0.02; non-Amish: r = 0.32, p = 0.04). Choroidal thickness was negatively correlated to NCI in both Amish (r = - 0.71, p = 0.001) and non-Amish (r = - 0.43, p = 0.01) groups. NCI was the most significant constant predictor of DV in both the Amish and non-Amish. CONCLUSIONS: Choroidal intensity, but not choroidal thickness, appears to be associated with drusen volume in Amish and non-Amish populations. These observations suggest that choroidal parameters beyond thickness warrant further study in the setting of AMD.